Oil price shocks, oil and the stock market volatility relationship of Africa's emerging and frontier markets - Molepo, Makgalemele (My University, 2017)
The study examined the relationship between oil price shocks, volatilities and stock indices in the African emerging markets. The ARDL and Bivariate BEKK GARCH models are used in this study. The countries examined are Botswana, Egypt, Mauritius, Morocco, Namibia, Nigeria, South Africa, Tanzania, Kenya, Ghana, Tunisia, and the MSCI’s World Index. The study shows a bidirectional relationship between oil price shocks for Nigeria and the MSCI, but unidirectional flow from oil price shocks to Botswana, Egypt, Mauritius, Morocco, Namibia, South Africa, Tanzania, Kenya, Ghana, and Tunisia. In addition, there is evidence of unidirectional volatility spill over from oil returns to Botswana, Namibia, Tanzania, Mauritius and Kenyan, Nigeria, Tanzania, Kenya and Ghana. Finally, the study found bidirectional volatility between oil and index returns in MSCI, South Africa, and Tunisia.
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2017
Keywords: Petroleum products--Prices; Financial crises; Stocks--Prices; Finance--Mathematical models